Oy Sözleşmeleri - İspir, Ömer Batuhan (My University, 2024)
Günümüzde ekonomik ve toplumsal öneme sahip olan şirketlerin, ortaklar tarafından yönetilme arzusu hep alışılagelmiştir. Ortakların, paydaşı olduğu şirketin yönetiminde söz sahibi olması, kritik konularda kendi istediği doğrultuda genel kurul kararlarının alınabilmesinin tek yolu, yeterince oy hakkına sahip olabilmektir. Genel kurulda sahip olduğu pay itibariyle çoğunluğu sağlayamayan ortaklar, genelde diğer ortaklar ile genel kurulda anlaşacakları yönde oy kullanarak şirketin yönetiminde aktif olma yolunu seçmektedirler. Taraflar, sadece birbirleri arasında hüküm doğuracak ve şirketi ilgilendirmeyen birer borçlar hukuku sözleşmesi yaparak bu amaca ulaşmaya çalışırlar. Akdedilen oy sözleşmeleri sadece sözleşmenin tarafını bağlamaktadır. Bu sebeple sözleşmenin ihlali halinde, sözleşmeden elde edilecek amacı tekrar tesis etmek oldukça zordur. Bu durum tarafları oy sözleşmesine uyulmasını sağlayacak amaçlara yöneltmektedir.

Nowadays, it is common for companies with economic and social importance to want to be managed by partners. The only way for partners to have a say in the management of the company of which they are stakeholders, and for general assembly decisions to be taken in line with their wishes on critical issues, is to have sufficient voting rights. Partners who cannot provide the majority in terms of their shares at the general assembly generally choose to be active in the management of the company by voting in a direction they agree with the other partners at the general assembly. The parties try to achieve this goal by making a law of obligations contract that will only affect each other and does not concern the company. Voting contracts concluded are binding only on the parties to the contract. For this reason, in case of breach of contract, it is very difficult to re-establish the purpose to be obtained from the contract. This situation directs the parties to aims to ensure compliance with the voting agreement. In our study, we will examine voting contracts, their features, functions in practice, their validity, measures to ensure compliance with voting contracts, the consequences of non-compliance with the contract, voting contracts containing foreign elements and voting contracts in foreign law.
Keywords: Commercial law; Hissedarlar; measures to ensure compliance with the voting agreements; Oy hakkı; oy sözleşmelerinin geçerliliği; oy sözleşmesi; oy sözleşmesine uyulmasını sağlayan önlemler Voting right; Oy verme; Özel Hukuk; Private Law; Stockholders; Ticaret hukuku; Turkey; Türkiye; validity of voting agreement; Voting; voting agreement